2006
DOI: 10.1002/ffj.1667
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oils of Rubia tinctorum L. aerial parts from Iran

Abstract: Hydro-distilled volatile oil from the aerial parts of Rubia tinctorum L. was obtained at yield of 0.1% w/ w based on dry weight. The oil was analyzed by a combination of GC and GC-MS. Thirty-four components were identified, constituting 96.4% of the oil. The major constituents in the oil were pentadecanal (20.2%), tridecanal (16.7%) and globulol (7.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Essential oils are seldom encountered in Rubiaceae. The few aromatic species belonging to this family generally contain volatile constituents in low yields, as exemplified by Morinda morindoides fresh leaves (0.2%) [10], Galium odoratum dried aerial parts (0.05%) [11], Rubia tinctorum dried aerial parts (0.1%) [12], Mitracarpus scraber fresh aerial parts (0.04%) [13], Randia mutadae flowers (0.02%) [14], or Gardenia jasminoides flowers (0.07%) [15]. Hydrodistillation of the fresh aerial parts of A. emirnense and A. perrieri in a Clevenger-type apparatus provided dark yellow essential oils with strong and pleasant smells in 0.035 and 0.022% (w/w) yield, respectively.…”
mentioning
confidence: 99%
“…Essential oils are seldom encountered in Rubiaceae. The few aromatic species belonging to this family generally contain volatile constituents in low yields, as exemplified by Morinda morindoides fresh leaves (0.2%) [10], Galium odoratum dried aerial parts (0.05%) [11], Rubia tinctorum dried aerial parts (0.1%) [12], Mitracarpus scraber fresh aerial parts (0.04%) [13], Randia mutadae flowers (0.02%) [14], or Gardenia jasminoides flowers (0.07%) [15]. Hydrodistillation of the fresh aerial parts of A. emirnense and A. perrieri in a Clevenger-type apparatus provided dark yellow essential oils with strong and pleasant smells in 0.035 and 0.022% (w/w) yield, respectively.…”
mentioning
confidence: 99%
“…The average yield of essential oil was 0.10 mL/kg. In previous studies of the Rubiaceae family plants, the yields of the essential oils of R. tinctorum , C. glabra , and P. leiocarpa were 0.10 mL/kg, 0.08 mL/kg, 0.10 mL/kg, respectively [ 38 , 39 , 40 ]. Moreover, the latest study found that five species of Rubiaceae plants yielded 0.24 mL/kg, 0.32 mL/kg, 0.08 mL/kg, 0.05 mL/kg, and 0.30 mL/kg, respectively [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The herb contains many polyphenol derivatives such as flavonoids and anthraquinones [13]. Several years ago its medicinal usefulness was discovered and the root of madder is used for the kidney and bladder stone treatment [1, 3, 4]. The observed activity is due to the presence of polyphenols and polyphenol glycosides which dissolve calcium oxalate, the foremost compound in kidney stones [5].…”
Section: Introductionmentioning
confidence: 99%